Auto-ignition of polyoxymethylene dimethyl ether 3 (PODE3) blended with diesel and gasoline via combustion under homogeneous charge compression ignition. (September 2021) - Lin, Qinjie; Tay, Kun Lin; Yang, Wenming
Highlights: PODE3 /diesel/gasoline blends in a HCCI engine are studied for the first time. High temperature kinetic reactions are dependent on cetane number of fuel blend. Oxygen from PODE3 helps promote better ignition when gasoline is added to PODE3 . Gasoline addition to PODE3 presents higher efficiency than diesel addition. PODE3 demonstrates high potential in encouraging clean combustion. Abstract: With high oxygen content and cetane number, PODE3 is a favorable renewable fuel for engines. PODE3 /diesel/gasoline blends in a HCCI engine are numerically studied for the first time. The effects of fuel blend ratio and equivalence ratio (ER) on auto-ignition are investigated. A highly compact and robust chemical mechanism has been implemented. Crank angle at which 50 percent of heat is released (CA50) displays higher sensitivity towards blend ratio in leaner mixtures with 50% PODE3 displaying a change of 12.31 CAD at 0.34 ER and only 6.19 CAD at 0.5 ER when made in comparison to their respective CA50 at 100% PODE3 . Furthermore, indicated thermal efficiency (ITE) is observed to be better with higher ER with 100% PODE3 having a 23.3% increase in ITE at 0.5 ER than at 0.34 ER, and is generally higher with increased PODE3 . Neat PODE3 displays lowest CO and highest CO2 for all cases, manifesting high oxidation reactivity. Additionally, acetylene levels are substantially lower for combustions at 0.5 ER as compared to 0.34 ER. Lastly, PODE3 yields only 2.04 × 10 −10 g/cycle and 5.67 × 10 −11 g/cycle of C2 H2 at 0.34 ER and 0.5 ER respectively. With nearly no soot precursors, PODE3 demonstrates high potential in encouraging clean combustion.